2021
DOI: 10.3389/fpsyg.2021.763046
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chinese College Students’ Physical Exercise on Life Satisfaction: The Chain Mediation Effect of Core Self-evaluation and Positive Emotion

Abstract: Physical exercise is an important way for college students to maintain their physical health, and life satisfaction is one of the important indicators of college students’ mental health. Therefore, this study aims to explore the relationship between physical exercise and life satisfaction of college students. Additionally, we also seek to demonstrate the chain mediating effects of core self-evaluation and positive emotion on this relationship. A total of 794 Chinese college students, 324 men and 470 women, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…A study suggested that stressful life events increased individual difficulty in emotion regulation and put them in a state of stress. Under stressful conditions, it was easier to regard mobile phones as an emotional venting tool, increase usage frequency, and then lead to academic burnout (Liu et al, 2019). Similar to mobile phone usage, people reported that they were more distracted and less productive in communication when phubbing occurred (Dwyer et al, 2017), and thus affected academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…A study suggested that stressful life events increased individual difficulty in emotion regulation and put them in a state of stress. Under stressful conditions, it was easier to regard mobile phones as an emotional venting tool, increase usage frequency, and then lead to academic burnout (Liu et al, 2019). Similar to mobile phone usage, people reported that they were more distracted and less productive in communication when phubbing occurred (Dwyer et al, 2017), and thus affected academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Data from previous studies point to a strong link between physical activity and life satisfaction among university students (Liu et al, 2021). In recent years, there has been an increase in research on the relationship between physical activity and life satisfaction, and the positive effects of physical activity on life satisfaction are gaining attention from researchers (Chen, 2005).…”
Section: The Association Between Physical Exercise and Life Satisfactionmentioning
confidence: 99%
“…Previous studies have shown that the level of personal life satisfaction is not only influenced by the individual’s internal emotions (such as anger, frustration), but also influenced by external social factors (such as work environment) and behavioral lifestyles (such as physical and cultural activities) ( Cruz-Ferreira et al, 2011 ). Among these influences, people’s behavior and lifestyles are of wide concern to society ( Arslan and Akkas, 2014 ; Liu et al, 2021 ). Physical exercise is a physical activity that aims to develop physical fitness, improve physical and mental health and enrich the diversity of one’s life through a variety of reasonable physical means according to one’s needs ( Han, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… 13 Studies have found a positive correlation between physical exercise and life satisfaction. 14 Physical exercise not only influences individuals’ social cognitive abilities through its unique group environment, but it also enhances cognition by improving physiological functions and mood states, thereby increasing individual life satisfaction. 15 Meaning in life refers to individuals’ perception and awareness of the nature of themselves and their existence, including the recognition and perception of things they deem important, 16 encompassing two dimensions: having meaning and seeking meaning.…”
Section: Introductionmentioning
confidence: 99%